Sublethal enantiotoxicity of MDMA on the development, teratogenicity, genotoxicity and swimming behaviour of zebrafish (Danio rerio) embryo - Ribeiro, Ondina (2024)
Background: Chiral psychoactive substances (PAS) as amphetamine-like substances are among the main group of drugs seized in Europe. The increased attractiveness of these drugs resulted in their widespread occurrence in the environment raising concern about their possible hazardous effects to non-target organisms [1, 2]. PAS metabolism in humans and biodegradation in wastewater treatment plants is stereoselective. Enantiomers of PAS may differ in environmental fate and toxicological effects [2, 3]. Understanding their enantiomer-specific toxicity and sublethal effects using several biomarkers is crucial for an accurate risk assessment of chiral contaminants. Objective: Investigate the potential enantioselective effects of 3,4-methylenedioxymethamphetamine (MDMA) in zebrafish (Danio rerio) embryos. Methods: For zebrafish 96-h assay, 50 fertilized eggs (≈ 3 hpf) were exposed to different concentrations of MDMA racemate and enantiomers ranging from 0.02 to 200 μg/L. Six replicates per test concentration and control were performed and organisms were exposed for 6 days. Embryonic development, malformations, genotoxicity and larvae swimming behaviour parameters were evaluated for MDMA. The range of concentrations for both organisms was selected to include environmental reported levels and higher concentrations to get insights into potential toxicity. Results: Regarding zebrafish, preliminary data showed an enantioselective effect with significant increase in the percentage of developmental malformations at 96 hpf in zebrafish larvae exposed to (S)-MDMA in comparison with (R,S)-MDMA and (R)-MDMA at the lower concentrations. An increase in larvae size was observed in the organisms exposed to the racemate in comparison to the enantiomers. Also, a significant increase in genotoxicity was observed in organisms exposed to racemate. Changes and enantioselective effects were also observed in swimming behaviour, (R)-MDMA inducing a reduction in the distance to the centre of the well compared to (S)-MDMA, and a decrease in inactive time in (S)-MDMA exposed organisms. Conclusions: This study showed the toxicity of MDMA towards zebrafish embryo, and importance of enantiotoxicity studies for a better risk assessment.